Podnikatelský záměr - Himer, Martin (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Diplomová práce se zabývá zpracováním podnikatelského záměru nové obchodní společnosti. Nejprve je definována podstata podnikatelského záměru a sepsány poznatky z literatury. Dalším bodem je analýza trhu. Následně je přistoupeno k samotnému návrhu, který obsahuje finanční a marketingový plán a případná rizika. Posledním bodem je ekonomické zhodnocení celého projektu.

Diploma thesis is engaged in elaboration of a business project concerning a brand-new corporation. First of all, the key-stone of this business project is defined and the findings from the literature retrieval are written down. The next point is the market analysis. Consequently is approached a actual proposal which contains a financial plan, marketing plan and eventual risks. The last point is an economical evaluation of the whole project.
Bussiness project
Keywords: SWOT analýza; internetový obchod; obchodní společnost; SWOT analysis; internet shop; corporation